Association between workers' compensation claim processing times and work disability duration: Analysis of population level claims data. Issue 10 (October 2019) - Gray, Shannon E.; Lane, Tyler J.; Sheehan, Luke; Collie, Alex
Highlights: Neurological or mental health conditions are most subject to processing delays. Greater delays in claim processing lead to longer disability duration. Existing work disability models need extension to include a time-based element. Abstract: Delays in workers' compensation claim processing (CP) times have been associated with reduced recovery and delayed return-to-work. This study aimed to (1) determine the injury, worker, and workplace factors associated with CP delays and (2) investigate whether CP delays are associated with longer disability duration after adjusting for these factors. Retrospective cohort analysis of Australian workers' compensation claims was conducted from 1st July 2009 to 30th June 2016 for objective (1) and to 30th June 2014 for objective (2). CP times were derived by calculating differences in days between: injury and lodgement dates (lodgement); lodgement and decision dates (decision) and; injury and decision dates (total). All CP times were shorter for younger workers and those with fractures or traumatic injury, and longer for those with neurological or mental health conditions, and other diseases. Claims from self-insured employers had shorter decision times. With increasing lodgement, decision and total time there was significantly higher hazard of longer disability duration. Findings suggest the need for more efficient claims management to ensure fewer barriers to claim lodgement or approval. This in turn should reduce disability duration and ensure improved return-to-work outcomes.